Application of Basic Welding Techniques Shield Metal Arc Welding (SMAW) to Improve the Capability of Forced Village Communities - Mohammed Riayadh (Collaborate Engineering Daily Book Series, 2023)
Most of the area of ​​this village is an area of ​​rice fields and fields. In the agricultural sector, some villagers have used mechanical, agricultural equipment that requires maintenance and repair by welding. In addition, welding is also often used in the livestock sector and for other purposes. Among the many types of welding, SMAW welding is the most popular and widely used both on a home and industrial scale. The welding process requires understanding the correct procedures, appropriate tools, personal protective equipment, and K3. Therefore, training guidance was held for the Force Village community to improve welding skills. The method used is providing material about welding, K3 and practice. The results of this training guidance activity show an increase in the skills and knowledge of the trainees, which can be seen from the results of the tests before and after the training.